2008
DOI: 10.1155/2008/957935
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Pressure Synthesis of Nanostructured Tungsten Oxide Crystalline Films

Abstract: We report the results of the ambient pressure synthesis of tungsten oxide nanowires and nanoparticles on AlN substrates using the hot filament CVD techniques. The morphologic surface, crystallographic structures, chemical compositions, and bond structures of the obtained samples have been investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), and Raman scattering, respectively. Different morphologies were observed for different substrate temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The band at 200-300 cm −1 has a stronger Raman signal than that one at ~800 cm −1 . This is different from that of WO [22][23][24]. In general, tungsten nitride forms together with little tungsten oxide.…”
Section: Basic Characterization Of Nanocomposite Materialsmentioning
confidence: 68%
“…The band at 200-300 cm −1 has a stronger Raman signal than that one at ~800 cm −1 . This is different from that of WO [22][23][24]. In general, tungsten nitride forms together with little tungsten oxide.…”
Section: Basic Characterization Of Nanocomposite Materialsmentioning
confidence: 68%
“…However, no similar phenomenon is observed from the stretching modes. Previous work indicated that spectral lines were blue shifts following an increase in the substrate temperature during synthesizing [ 43 ]. In general, the blue shift in the Raman peaks should result from the change in crystal symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…This simple and cost-effective synthesis technique was different from the method used in our previous work [ 40 , 41 , 42 , 43 ]. In the present work, the tungsten oxide composites were synthesized using a simple hot-filament CVD technique where the tungsten filament itself acted as a precursor for tungsten oxide, without using any catalyst or other tungsten-containing compound precursors.…”
Section: Methodsmentioning
confidence: 99%
“…19) Such phase transition, stoichiometric change, and oxidation-reduction reactions were reported previously. 20) These factors enhance solid chemical reactions and affect the synthesized nanoparticles and photocatalytic abilitiy. 19) To investigate the baking temperature dependence of synthesized nanoparticles on the crystal structure, we measured the XRD spectra of the samples.…”
Section: Resultsmentioning
confidence: 99%